FREQUENCY OF VEIN GRAFT OCCLUSION AFTER BYPASS SURGERY IN PATIENTS UNDERGOING CORONARY CT ANGIOGRAPHY WITH ANGINAL SYMPTOMS - Siddiqui, Abdul Hameed; Ahmed, Imran; Khan, Sajid Ali; Abbas, Shahid; ., Hasnain; Farhan, Shaheer; Tuyyab, Farhan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the frequency of vein graft occlusion after bypass surgery in patients undergoing coronary computerized tomography angiography with anginal symptoms.Study Design: A retrospective longitudinal study.Place and Duration of Study: Computerized Tomography Angiography department, Armed Forces Institute of Cardiology/ National Institute of Heart Disease, Rawalpindi Pakistan, from Jan to Jun 2021.Methodology: A total of 109 patients having angina symptoms after coronary artery bypass graft. For this purpose, we performed computerized tomography angiography for graft study to assess the patency/occlusion of bypass grafts and to rule out possible cause of anginal symptoms. Along with that, we also assessed the co-morbids, i.e. DM, HTN, Gender and age factor which could be the possible risk factors in occlusion of the grafts.Results: A total of 109 patients according to the inclusion criteria were enrolled in the study. The mean age of the patient population was 61.55 ± 9.53. Among which 92 (84.4%) were males and 17 (15.5%) were females. Fifty (45.8%) patients were hypertensive while 55 (50.4%) were diabetic. Forty one (37.6%) had past history of coronary artery bypass graft with duration of 1-5 years followed by 29 (26.6%) patients with duration of 6-10 years and 21 (19.3%) patients had duration in 11-15 years. Among the study population 39 (35.8%) had left internal mammary artery-LAD, SVG-OM, SVG-RCA grafts followed by 13 (11.9%) patients who had left internal mammary artery to LAD and SVG to OM while only 5 patients had left internal mammary artery to LAD as lone graft. Out of 105 patients out of 109 (96.3%) received mammary graft. Two patients also received right internal mammary graft. Graft occlusion occurred in SVG-RCA among 34 (31.2%) patients followed by 17 (15.6%) patients who had graft occlusion in SVG-OM. As far as the number of grafts is concerned, 66 (60.6%) had three grafts while 26 (23.93%) had two grafts and 12 (11%) had four grafts and only 5 (4.58%) had one graft. Sixty six (60.5%) patients had symptoms of angina CCS class I and II while 27 (24.7%) patients had presented with acute coronary syndrome (both STEMI and NSTEMI).Conclusion: Less than ideal patency rate of saphenous vein grafts associated with adverse outcome reminds the necessity of performing technically perfect coronary artery bypass surgery alongwith special emphasis on secondary prevention. Further progress must be made in preventing intimal injury during harvesting and exposure to arterial pressure and platelet adherence resulting in development of intimal hyperplasia to improve graft patency.